Experimental Investigation of Poultry House Heating System Enhanced with Heat Storage system - Derouche Intissar; Ammari Rawane (University of Shahid Hama Lakhdar - El Oued, 2025)
"This thesis presents an experimental study of a heating prototype for poultry houses in the arid regions of Algeria, specifically in El Oued. A custom-designed solar thermal collector is installed on the poultry house roof. The model features insulated sandwich panel walls and a wooden-framed heating unit mounted on the roof. The heating system includes a primary layer of black-painted iron plates to maximize solar absorption. A phase change material (PCM) is placed on this layer to store thermal energy, allowing the poultry house to remain heated during non-sunny hours. This assembly is covered by a secondary layer of glass plates functioning as a flat-plate solar collector. The system design enables air intake from one side, circulation beneath the iron plates, and outlet through ducts on the opposite side. The airflow beneath the solar collector, combined with the PCM, delivers warm air into the poultry house. A ventilation system assists in evacuating air to the outside. Measurements were taken starting at 8 a.m. The results were compared to a system without PCM and were thoroughly analyzed and discussed. This method enhances productivity and reduces energy costs. " يقدم هذا البحث دراسة تجريبية لنموذج أولي لنظام تدفئة مخصص لحظيرة الدواجن في المناطق الجافة من الجزائر وتحديدا في منطقة الوادي. تم تركيب مجمع شمسي حراري مصمم خصيصا على سطح الحظيرة. يتكون النموذج من جدران مصنوعة من ألواح عازلة (ساندويتش)، بالإضافة إلى وحدة تسخين بهيكل خشبي مثبتة على السطح. يتضمن نظام التسخين طبقة أولى من صفائح الحديد المطلية باللون الأسود لتعزيز امتصاص الطاقة الشمسية. وقد تم تركيب مادة متغيرة الطور (PCM) فوق هذه الطبقة لتخزين الطاقة الحرارية، مما يتيح تسخين الحظيرة خلال ساعات غياب أشعة الشمس. وتغطي هذه التركيبة طبقة ثانية من الزجاج تعمل كمجمع شمسي مسطح. يسمح التصميم بدخول الهواء من جانب واحد، ثم يتدفق تحت صفائح الحديد ويخرج من خلال قنوات في الجهة المقابلة. يسهم تدفق الهواء المسخن تحت المجمع، إلى جانب تأثير الـ PCM ، في إدخال هواء دافئ إلى داخل الحظيرة، ويقوم نظام التهوية بطرد الهواء إلى الخارج. قمنا بعدة عمليات قياس من الساعة الثامنة صباحًا. وقد تمت مقارنة النتائج مع نظام لا يحتوي على PCM ، وتم تحليل النتائج ومناقشتها. تؤكد النتائج أن هذا النظام يمكن أن يحسن من إنتاجية الحظيرة ويقلل من التكاليف الطاقوية.
Master's thesis specializing in energy.2025
Keywords: thermal collector; poultry; heating; energy efficiency.; مجمع حراري دواجن، تدفئة، كفاءة طاقوية.